The THE USE OF ORGANIC IMAGERY IN THE NOVEL MAYBE EVERYTHING - SASTRAWAN, EDY (ID Solutions, 2023)
This study focused on the analysis of organic imagery in the novel entitled Maybe Everything. The objective of this study is to classify and identify the dominant feelings of the organic imageries in the novel entitled Maybe Everything. This study used the theory by Perrine in Sound & Sense (1974) about the types of imagery, specifically organic imagery as the guidance in conducting the analysis. The data of this study were collected by using observation method and analyzed by using qualitative research method. The finding of this study were presented in formal and informal method. The result of this study shows that there are a total of 20 organic imageries found in the novel entitled Maybe Everything. The types of feeling within the organic imagery include the feeling of happiness, sadness, anger, depression, surprisement, embarrassment, amazement, fear, maturity, and pain. The study concludes that organic imagery is used in the novel entitled Maybe Everything to focus the depiction of the main character through his thoughts and feelings to match with the theme of the novel.